Analysis Factors That Influence Associate Nurses Toward Decubitus Prevention On Bed Rest Patient In Intensive Care Unit At Ulin Banjarmasin Hospital - Meti Agustini; Dyah Yarlitasari Nurhikmah (IJNP (Indonesian Journal of Nursing Practices), 2018)
Background: Hospital put patient safety as priority such as decubitus prevention to provides excellent service. The incidence of decubitus commonly occurs, such as in Western Europe generally occurs about 49%, 22% in North America, 50% in Australia, 29% in Jordan, and 33% in Indonesia. Nursing interventions to prevent decubitus is an indicator to assure the quality of nursing care. Nurses influenced by various factors toward decubitus prevention. Objectives: Aim’s of this study is to analyze the factors that influence nurses through decubitus prevention on bed rest patient. Methods: The population was all nurses in Intensive Care Unit at Ulin Hospital Banjarmasin (n=30)  this study used a cross sectional approach. Instrument research is a questionare and abservastion sheet which adopted from NPUAP 2014. The statistical test used multiple logistic regression with significance level of 0,05. Results: A multivariate results found that factors associated with decubitus prevention are knowledge (0,401), attitude (0,464), encouragement nurses (0,530), and facilities and infrastructure (0,530), p-value 0,05.  Conclusions: The most related factors that influence toward decubitus prevention are knowledge, attitude, facilities and infrastructure, and encouragement nurses. Keywords: decubitus prevention, facilities and infrastructure support, fellow nurse supports, knowledge, nurse’s attitude